2021
DOI: 10.1021/acsami.1c05660
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating MoO3 Patches into a Ni Oxyhydroxide Nanosheet Boosts the Electrocatalytic Oxygen Evolution Reaction

Abstract: The electrocatalytic oxygen evolution reaction from H2O (OER) is essential in a number of areas like electrocatalytic hydrogen production from H2O. A Ni oxyhydroxide nanosheet (NiNS) is among the most widely studied OER catalysts but still suffers from low activity, sluggish kinetics, and poor stability. Herein, we incorporate MoO3 patches into NiNS to form a nanosheet with an intimate Ni–Mo interface (NiMoNS) for the OER. The overpotential at 10 mA cm–2 and Tafel slope on NiMoNS (260 mV, 54.7 mV dec–1) are lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 57 publications
(215 reference statements)
0
21
0
Order By: Relevance
“…It is clearly observed that the peaks at 855.83 eV and 857.51 eV are ascribed to the 2p 3/2 of Ni 2+ and Ni 3+ , respectively, and their satellite peaks locate at 861.80 eV and 865.31 eV. For Ni 2p 1/2 , the peaks occur at 873.40 eV and 875.76 and are attributed to the Ni 2+ and Ni 3+ species with their satellite peaks at 879.57 eV and 882.59 eV, respectively [32][33][34]. The lower curve of Figure 4d displays the XPS spectrum of Mn 2p, which can be separated into Mn 2+ , Mn 3+ , and Mn 4+ components at 639.09, 641.23, and 643.28 eV, respectively [35,36].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is clearly observed that the peaks at 855.83 eV and 857.51 eV are ascribed to the 2p 3/2 of Ni 2+ and Ni 3+ , respectively, and their satellite peaks locate at 861.80 eV and 865.31 eV. For Ni 2p 1/2 , the peaks occur at 873.40 eV and 875.76 and are attributed to the Ni 2+ and Ni 3+ species with their satellite peaks at 879.57 eV and 882.59 eV, respectively [32][33][34]. The lower curve of Figure 4d displays the XPS spectrum of Mn 2p, which can be separated into Mn 2+ , Mn 3+ , and Mn 4+ components at 639.09, 641.23, and 643.28 eV, respectively [35,36].…”
Section: Resultsmentioning
confidence: 99%
“…Nanomaterials 2022, 12, x FOR PEER REVIEW 8 of 14 attributed to the Ni 2+ and Ni 3+ species with their satellite peaks at 879.57 eV and 882.59 eV, respectively [32][33][34]. The lower curve of Figure 4d displays the XPS spectrum of Mn 2p, which can be separated into Mn 2+ , Mn 3+ , and Mn 4+ components at 639.09, 641.23, and 643.28 eV, respectively [35,36].…”
Section: Resultsmentioning
confidence: 99%
“…CV curves in the non-Faradaic region at different scan rates are next explored to further compare the GOR performances of Cu/C-0 and Cu/C-60 by using double layer capacitance ( C dl ) and electrochemical active surface area (ECSA) ( Yang et al, 2020 ; Liu et al, 2021 ). Figures 2G,H illustrates the CV curves at scan rates from 40 to 160 mV s −1 for Cu/C-0 and Cu/C-60, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…4−7 The electrocatalytic anodic reaction in water splitting through OER and the cathodic reaction in water splitting through HER have drawn tremendous attention because the generated H 2 can be utilized as a renewable and clean energy source. 2,8−16 Generally, research on various transition-metalbased composite oxides has emerged in recent years because of their cost effectivity and different applications such as water electrolysis, 3,17,18 Li-ion batteries, 19,20 solar cells, 21 and so forth. OER involves the transfer of four electrons for the evolution of an O 2 molecule, whereas for HER, transfer of two electrons takes place.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The increasing demands and environmental issues of consuming fossil fuels have led scientists to consider alternative possibilities for developing sustainable and clean energy technologies to meet the needs for higher global energy consumption. Thus, extensive efforts have been devoted for the development of a new energetic network connecting the large-scale use of renewable resources. Thus, electrocatalytic oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) have been considered as one of the most suitable and fundamental reactions in the energy research area. The electrocatalytic anodic reaction in water splitting through OER and the cathodic reaction in water splitting through HER have drawn tremendous attention because the generated H 2 can be utilized as a renewable and clean energy source. , Generally, research on various transition-metal-based composite oxides has emerged in recent years because of their cost effectivity and different applications such as water electrolysis, ,, Li-ion batteries, , solar cells, and so forth. OER involves the transfer of four electrons for the evolution of an O 2 molecule, whereas for HER, transfer of two electrons takes place.…”
Section: Introductionmentioning
confidence: 99%